2020
DOI: 10.26579/jocress.396
|View full text |Cite
|
Sign up to set email alerts
|

Covid 19 Bağlamında Uzaktan Eğitim ile İlgili Yapılan Bazı Çalışmaların Değerlendirilmesi

Abstract: World Health Organizations (WHO), (2020). WHO announces COVID-19 outbreak a pandemic. http://www.euro.who.int/en/health-topics/healthemergencies/coronavirus-covid-19/news/news/2020/3/whoannounces-covid-19-outbreak-a-pandemic,web adresinden 3 Temmuz 2020 tarihinde edinilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Digital parents should be able to set rules and limits regarding their children's use of digital devices, as well as embody the parent profile that can be exemplified as good role models (Akbaş Zeybekoğlu & Dursun, 2020). In order to raise socially, emotionally, and psychologically healthy individuals, parents need to be aware of the risks their children may face in digital platforms, have the competencies to protect them against these risks, and ensure that they can benefit from the opportunities offered by digital platforms (Hark Söylemez, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Digital parents should be able to set rules and limits regarding their children's use of digital devices, as well as embody the parent profile that can be exemplified as good role models (Akbaş Zeybekoğlu & Dursun, 2020). In order to raise socially, emotionally, and psychologically healthy individuals, parents need to be aware of the risks their children may face in digital platforms, have the competencies to protect them against these risks, and ensure that they can benefit from the opportunities offered by digital platforms (Hark Söylemez, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the related literature, there are some studies concluding that instructors need training on issues such as content development in distance education, use of the system and ensuring interaction (Bilgiç et al, 2011;Bozkurt, 2020;Erkut, 2020;Gürer et al, 2016;Karadağ, & Yücel, 2020). Also, there are studies which identified that instructors were incompetent in distance education requirements and emphasized the importance of training instructors in terms of the adoption and effectiveness of distance education (Can, 2020;Düzakın, & Yalçınkaya, 2008;Hark-Söylemez, 2020;Kayaduman, & Demirel, 2019;Yıldız, 2015). In addition, it was reported that educators were not competent in online education digital technologies, and regular in-service training should be provided for instructors (Ak et al, 2021).…”
mentioning
confidence: 99%